Symbiosis: burnout syndrome versus the efficiency of labor development in health institutions - Jiménez - Rodríguez , Luis Alfredo; Gamboa - Suarez , Ramiro; Jimenez – Ospina, Johao Sebastian (Universidad Francisco de Paula Santander, 2023)
Objective: To determine the Burnout Syndrome in the human assistance talent that works in institutions that provide health services of medium and high complexity, taking into account that professional burnout is the most serious manifestation of work stress, it is necessary to identify it early to achieve a timely and pertinent intervention to improve working conditions. Method: A positivist paradigm was used, with a Quantitative approach (Causes and effects based on numerical data), descriptive type of cross-sectional design, to a population of 3 institutions providing health services of medium and high complexity in the municipalities of Neiva Huila. –Girardot Cundinamarca and Ocaña norte de Santander, The material used and applied was the CESQT survey, with a content of 20 items. Results: The sociodemographic variables and those of the instrument were known to tabulate the data in the Excel document and then progress was made in the statistical instrument where professional burnout due to the syndrome generates boredom, depression, anxiety, loss of self-esteem and personal frustration. , manifesting itself in a cognitive, emotional and behavioral way, as a response to chronic work stress Conclusions: Burnout Syndrome can be defined as a silent pathology to which any worker is exposed and that can lead to serious effects if it is not detected, treated and cured in time.